DIFFERENCES OF SALIVARY PH AFTER CONSUMING PACKAGED LIQUID COW’S MILK AND PACKAGED LIQUID SOY MILK IN THE FACULTY OF DENTISTRY, ANDALAS UNIVERSITY - Hestia Warti; Nila Kasuma; Hidayati Hidayati (Faculty of Dentistry Universitas Andalas, 2016)
Saliva is a complex oral fluids. Normal salivary pH ranges from 6.4- 6.9. A diet rich in carbohydrates can cause changes in the pH of saliva. Milk is a food that contains almost all the nutrients such as carbohydrates, proteins, minerals and vitamins. The purpose of this research is to know the differences of salivary pH after consuming packaged liquid cow’s milk and packaged liquid soy milk. This study was an experimental study using pretest-posttest study design. The samples collected 22 people. Each sample drank 250 ml of packaged liquid cow’s milk and packaged liquid soy milk for 1 minute. There is no significant decrease in salivary pH (p>0,05) after consuming packaged liquid cow’s milk. There is significant decrease in salivary pH (p<0,05) in the 5 minutes after consuming packaged liquid soy milk.. Keywords : salivary pH, packaged liquid cow’s milk, packaged liquid soy milk